FATIGUE CRACK GROWTH LIFE ANALYSIS OF NICKEL-BASE SINGLE CRYSTAL TURBINE BLADE TENON - ZHANG ZhongKui (Jixie qiangdu)
Based on the work status of the aero-engine turbine blade,the contact fatigue tests of modeling specimens of tenon / groove were carried out. A fatigue crack growth life model of the modeling specimens was established. The crystallographic finite element program was implemented to study the stress field of the tenon / groove. Crack growth lives obtained from the finite element analysis had a good agreement with the results of experiment. It was demonstrated that the life model could be used in engineering to predict the remaining life of turbine disk.